PENGARUH KOMUNIKASI INTERPERSONAL DAN LINGKUNGSN KERJA TERHADAP KINERJA KARYAWAN PT. EURO MANAGEMENT INDONESIA - Syifa Aulia Gumay; Agus Hermani DS (Jurnal Ilmu Administrasi Bisnis, 2018)
PT. Euro Management Indonesia as an educational consultant services company have some low level performance of employees such as not good in giving directives or guidance or work orders, some work space is not adequate, and the achievement of quality and quantity targets that have not maximized. It is allegedly due to the existence of interpersonal communication and work environment employees are still considered not good. The aims of this study to determine how the influence that given by interpersonal communication and work environment to the performance of employees of PT. Euro Management Indonesia. Type of this research is explanatory research, with 50 respondents of samples. Used questionnaire as data collecting with Likert measurement scale. In the data analysis method used is test of validity and reliability, correlation coefficient (R), regression test, coefficient of determination (R2 ), significance of t test and F test by using SPSS 20.0. The results of this research shows that interpersonal communication and work environment severally has significant, strong and positive influence toward employee performance. Two variables has been tested gradually or even together show that interpersonal communication (0,682) and work environment (0,678) simultaneously have strong relation with employee performance. The amount of contribution value (R2 ) by interpersonal communication is greater than work environment, coefficient of determination value (R2 ) for interpersonal communication is 46,5% and work environment is 46%. The company should be improves interpersonal communication and work environment so high performance will be reached, such as the company leader i provide work orders mmediately and employees convey to the leadership when facing obstacles and give or ask for help to other employees immediately. Moreover by equipping work equipment, expanding and adding workplace lighting, employees will feel comfortable and undisturbed in doing the work, so they will get better job results.